Informations et jeux d’acteurs autour d’une politique environnementale : le cas du programme de paiements pour services environnementaux au Costa Rica - Denis Pesche; Jean-François Le Coq (Développement Durable et Territoires)
Information plays a role in policy design and implementation. A huge quantity of diverse information has been produced on the Payment for Environmental Services Program (PESP) in Costa Rica. This paper proposes a categorization of the information based on six information flows. Among them, we show that the flow of information produced at national level and/or managed by the program contributes to minor changes. Conversely, information flows with international dimensions, are involved in more strategic changes. The article also highlights the fact that national and international dimensions are generally nested through the interplay of actors who contribute, through the mobilization of information, to trigger the changes observed in the PESP.